2011
DOI: 10.1088/0957-4484/22/25/254027
|View full text |Cite
|
Sign up to set email alerts
|

Scaling limits of resistive memories

Abstract: This paper is intended to provide an expository, physics-based, framework for the estimation of the performance potential and physical scaling limits of resistive memory. The approach taken seeks to provide physical insights into those parameters and physical effects that define device performance and scaling properties. The mechanisms of resistive switching are based on atomic rearrangements in a material. The three model cases are: (1) formation of a continuous conductive path between two electrodes within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 43 publications
0
61
0
2
Order By: Relevance
“…The device fabrication process for our memristive RF switches is also simpler as compared with other devices. Further scaling of the device, such as shrinking the gap size, will lead to optimized switching behaviour such as longer endurance and lower power consumption 44,45 with no degradation to the RF performance, provided the ON-state resistance is dominated by the filament and not other effects. It is necessary to engineer the location and geometry of the metallic filaments for even lower ON-state resistance, to enhance the device endurance, and to reduce the energy required for each switching event.…”
Section: Discussionmentioning
confidence: 99%
“…The device fabrication process for our memristive RF switches is also simpler as compared with other devices. Further scaling of the device, such as shrinking the gap size, will lead to optimized switching behaviour such as longer endurance and lower power consumption 44,45 with no degradation to the RF performance, provided the ON-state resistance is dominated by the filament and not other effects. It is necessary to engineer the location and geometry of the metallic filaments for even lower ON-state resistance, to enhance the device endurance, and to reduce the energy required for each switching event.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 This leads to several theoretical models regarding not only the fundamental processes 37,38 but also device aspects e.g. scaling limitations, 39 programming kinetics 37,40,41 and multilevel switching. 9,39,42,43 In the context of commercial applications, the switching speed is crucial for device operation and the same rate limiting factors e.g.…”
Section: Introductionmentioning
confidence: 99%
“…scaling limitations, 39 programming kinetics 37,40,41 and multilevel switching. 9,39,42,43 In the context of commercial applications, the switching speed is crucial for device operation and the same rate limiting factors e.g. interfacial processes, nucleation, transport etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews of this topic can be also found. [1][2][3][4][5] Note that material systems and physical mechanisms are not discussed in this article but will be reviewed in the articles in this issue.…”
Section: Introductionmentioning
confidence: 99%